Impact of the use of some mobile software on the level of skill and cognitive learning of some volleyball skills - Alaa Naji, Saif; Abdulrazzaq Noori, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
Mobile is modern technologies that have emerged recently and spread in all countries which has become available to most of the community, many types and varied services provided and developed methods has been used, And because volleyball is difficult skills so the researcher thought of the possibility of using this technique to exist out of time and space to a wider and more enjoyable world and thus can improve the level of skillful learning and knowledge of some volleyball. The program using the mobile phone has a positive impact on the performance of skilled Students Sample Search the use of the mobile phone as an assistant in the teaching of the skills of volleyball has a clear impact in the collection of information and knowledge students and reception for longer. The use of the mobile phone is a useful method in the educational process to help students to obtain further information on the article to be studied. The need for the use of the mobile phone is due to its impact in the entrenchment of educational material to students. There are uses of the mobile phone and its applications in other lessons. Conduct more experimental research using other modern applications and compare it with Viper and Watts to reach the highest possible level in teaching different sports activities. Interest in the work of training courses for teachers and workers in the sports field within the institutions.